The Effect of HIIT Brisk Walk and Intermittent Fasting Training on Body Composition - Dhaniswara, Nalendra; Resti Nurpratiwi; Bayu Pradana Bachtiar Saputra; Mohammad Alvi Syahri; Muhammad Fatah; Enarnimas Dwi Ratna Damayanti; Anisa Galu Utari; Ahmad Panca Himawan; Moch. Faisol; Mohammad Reyhan Dwi Pradana; Ashadi, Kunjung; Kusnanik, Nining Widyah; Bayu Agung Pramono (Journal of Sport and Exercise Science, 2024)
Purpose: Intermittent Fasting is currently a supporting strategy for weight loss that is widely used because indirectly energy needs are obtained from burning fat in the body. The purpose of this study was to evaluate the effect of the combination of Intermittent Fasting with physical activity, researchers used the type of brisk walk exercise in the weight loss program and changes in body composition in each individual. Materials and Methods: The research method was carried out by conducting an exercise program for 12 periods with measurements of body weight, body mass index, body fat, body water, and visceral fat as the main parameters. Result: The results showed that the combination of Intermittent Fasting with physical activity, especially brisk walking, had a significant positive impact on weight loss and body composition regulation. Conclusion: It can be concluded in this study that the combination method of Intermittent Fasting with physical activity is quite good in reducing body weight, body mass index, body fat, body water, and visceral fat.